Just keep clicking Till You Find It: Building a Library Digital Collection Interface with Browsing in Mind - Gueguen, Gretchen (East Carolina University, 2009)
This session will explore how East Carolina University's Joyner Library developed an interface to their digitized special collections to facilitate user browsing. The library's digital collections contain thousands of items digitized from hundreds of collections – in some cases only one or two items are digitized from a collection. This hodge-podge approach is a result of the library's image management practices which attempt to store materials digitized on a daily basis (for patron requests, preservation concerns, publication or exhibits, etc.) into the publicly available digital repository. As the repository was being developed, the staff of Joyner Library decided that the traditional approach to presenting digitized special collections materials as a sort of online "exhibit" where materials are selected to illustrate a theme or to systematically convert an entire collection to the digital format would not work. Instead, the staff experimented with different ways to enhance user browsing through materials. They looked to the world of commercial websites, next generation catalog interfaces, and social networking sites to develop a suite of navigation tools that enhance serendipitous discovery using their own home-grown solutions that are built on top of an SQL database and an XML database. The final collection interface includes: broad thematic "collections", "tag cloud"-style navigation, and a faceted-browsing refinement tool, all developed from cataloguer-created subject headings; hyperlinked terms in item records to facilitate broadening searches; links back and forth between collection finding aids and other digital resources at the library; user commenting and tagging of resources to begin to integrate emerging folksonomies. The session will describe the technologies and techniques used to develop these tools, examine some of the benefits and drawbacks to this approach, and discuss user feedback collected through usability testing, website statistics, and reference interaction.
Keywords: Digital libraries; Interface design